Profiles of Students’ Numeracy Literacy Based on Wholist-Analytic Cognitive Styles: Implications for Differentiated Learning Strategies - Heni Pujiastuti; Dini Dahlia; Anwar Mutaqin (AL-ISHLAH: Jurnal Pendidikan, 2025)
Numeracy literacy is a vital 21st-century competency, yet Indonesian high school students often underperform, especially in data interpretation and contextual reasoning. Individual differences, such as cognitive styles, may influence students’ approaches to numeracy tasks. This study explores how Wholist–Analytic cognitive styles relate to students’ numeracy literacy and examines the implications for differentiated instruction. This qualitative phenomenological study involved 12 tenth-grade students purposively selected from two public high schools representing different achievement categories. Students were categorized into Wholist or Analytic cognitive styles using the Matching Figure Test and Embedded Figure Test. Each group included students with high, medium, and low numeracy abilities. Data were collected through cognitive style assessments, numeracy literacy tests, interviews, and observations. Analysis was conducted using triangulation and NVivo 12 Plus software. Wholist students demonstrated strengths in understanding global contexts but often overlooked numerical precision, especially among lower-achieving students. In contrast, Analytic students applied systematic problem-solving strategies but struggled to connect results with contextual meaning. High-achieving students in both groups successfully integrated their cognitive tendencies with strong numeracy skills, while lower-achieving students exhibited consistent challenges regardless of style. The findings suggest that cognitive style alone does not determine numeracy success; rather, its interaction with skill level is critical. Differentiated learning strategies—such as problem-based learning, visual scaffolding, and technology integration—can address these differences. Educators should tailor instruction to students’ cognitive profiles to enhance numeracy outcomes.